Green quaternary concrete composites: Characterization and evaluation of the mechanical properties. (29th May 2018) - Dave, Niragi; Misra, Anil Kumar; Srivastava, Amit; Sharma, Anil Kumar; Kaushik, Surendra Kumar
Abstract : Industrial byproducts such as fly ash (FA), silica fume (SF), ground granulated blast furnace slag (GGBS), metakaolin (MK), and lime powder (LP), popularly known as supplementary cementitious materials (SCMs), have been extensively used in the manufacturing of cement and cement products in binary and ternary modes. In the present study, attempt has been made to develop a new sustainable green quaternary binder by partially replacing ordinary Portland cement (OPC) with different percentages of SCMs and find the optimum mix that can provide the best results in terms of mechanical as well as durability properties. The motivation is to reduce our dependency on OPC to reduce carbon foot print and utilizing these industrial byproducts for the sustainable development. Different compositions of quaternary binders were prepared and their physical, mechanical, and durability properties were studied and compared with the OPC and binary cement product pozzolanic Portland cement (PPC). The mechanical properties of concrete prepared with these OPC, PPC, and quaternary binders were also studied and it is established that the concrete mixtures prepared with quaternary binders provided better results and proved to be more economical. It is concluded that quaternary binders (a) OPC70% + FA15% + SF7.5% + GGBS7.5%, (b) OPC70% + FA15% + SF7.5% + MK7.5%, (c) 50%OPC + 30%FA + 10%SF + 10%GGBS, and (d) 50%OPC + 30%FA + 10%SF + 10%MK have produced relatively better strength, improved durability, and resistance to sulfate attack. These findings were also supported with the microstructural studies of hardened concrete of M20 grade using scanning electron microscope (SEM) and X‐ray diffraction (XRD).